LEARN, LEARN, LEARN: UNDERSTAND AND APPRECIATE THE PROCESS OF LEARNING - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
Often times, the new batch of students have been reminded of their underlying responsibility at the university, which is to learn, learn and learn. Learning involves numerous processes that need to be understood and done correctly to achieve the desired impact during the duration of study in the university.